Correspondência verbal: uma revisão de literatura de 2009 a 2021 e o efeito de sessões sucessivas e de perda de fichas sobre o brincar e o relatar de crianças - Melo, Luiz Felipe Silva (2022)
This doctoral dissertation carried out a 2009 to 2021 systematic review to update the literature review on verbal correspondence. As a result, it was pointed out an increase in the number of publications in verbal correspondence, mainly in Brazilian vehicles, as well as a maintenance of settings and participants, when compared to reviews that analyzed the subject up to 2008. The dissertation also presents an experimental study with the aim of verifying a procedural modification in the Gomes et al.’s study (2018), using more than one collection session per day in regard to play and reporting tasks with four 5- and 6-year-old children in a single-subject design. There were four experimental phases: baseline; punishment for not playing; punishment of noncorrespondence; and noncontingent reinforcement. The use of successive sessions for verbal correspondence research using the play task seemed to be effective in reducing collection time. However, most of the participants kept the corresponding report throughout the study, and only one of the participants started to report according to the programmed experimental phases. The effect created by the withdrawal of tokens in the second phase of the study may have contributed to the need for a greater number of sessions in the phase of punishment of non-correspondence, in order for the participant to emit corresponding reports again